ANALISIS PERENCANAAN PRODUKSI DISAGREGAT FAMILY DVD PADA PT XYZ - Prasetya, Hans; Nurhasanah, Nunung (Industrial and Systems Engineering Assessment Journal (INASEA), 2007)
The most recently problem that used to happened at PT XYZ is about production planning (Master Production Scheduling). Production planning in this company always takes so many times. To solve the problem, this research was trying to develop a disaggregate production planning. The steps were, demand forecasting, production capacity planning, and disaggregate planning. Double moving average, double exponential smoothing, and decomposition method were used to forecast demand. Least cost and stepping stone were the two methods from transportation model that were used to solve the production capacity planning. Hax and Meal method were used to solve a disaggregate planning.